Islamic green accounting concept: Integrasi green accounting dan maqashid syariah untuk keberlanjutan keuangan islam - Septi Purwaningsih; Nur Indah Wardani; Alfarisi Akbar Efendi; Destin Alfianika Maharani (Nur Science Institute, 2026)
Climate change and environmental degradation require the financial sector to play an active role in supporting sustainability. Islamic finance has significant potential due to its foundational values that align with the principles of sustainable development. Contemporary Islamic accounting practices remain largely focused on formal compliance and have not yet comprehensively integrated environmental aspects. This study aims to analyze the integration of Green Accounting with the principles of Maqashid Syariah and Islamic environmental ethics, and to develop a conceptual framework for Islamic Green Accounting. This research adopts a qualitative approach through a systematic literature review of 32 selected articles sourced from Google Scholar (2015-2025) with the keywords Green Accounting, Maqashid Syariah, Islamic Finance, and ESG. The analysis employs content analysis and concept mapping, grounded in the Maqashid Syariah framework. The findings indicate strong alignment between Green Accounting and Maqashid Syariah, particularly in protecting life, progeny, and wealth. This study proposes a conceptual framework of Islamic Green Accounting that positions Maqashid Syariah as the value foundation, Green Accounting as the technical instrument, and sustainability as the ultimate objective.